2021
DOI: 10.18502/ijm.v13i4.6971
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of multidrug-resistant non-fermentative Gram-negative bacilli harboring bla and bla metallo-beta-lactamase genes in Birjand, south-east Iran

Abstract: Background and Objectives: Non-fermentative Gram-negative Bacilli (NFGNB) is known as a major cause of health- care-associated infections with high levels of antibiotic resistance. The aim of this study was to investigate the antibiotic resistance profiles and molecular characteristics of metallo-beta-lactamase (MBL)-producing NFGNB. Materials and Methods: In this cross-sectional study, the antibiotic resistance profile of 122 clinical NFGNB isolates was determined by the Kirby-Bauer disk diffusion and m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 30 publications
1
5
1
Order By: Relevance
“…This was similar to the study by al charrakh et al, were P. aeruginosa was a predominant pathogen among various NFGNB [15]. In our study, P. aeruginosa showed increased prevalence the blaNDM gene (50%) followed by blaVIM gene (25%) and blaIMP gene (25%), these findings were similar to the study by Namaei et al, blaNDM gene (40%) followed by blaVIM gene (29%) and blaIMP gene (13%) [16,17]. In our study, for A. baumannii we observed an increased prevalence of blaOXA-23 gene(78%) followed by blaOXA-58 (56%) and blaNDM gene(33%).…”
Section: Discussionsupporting
confidence: 92%
“…This was similar to the study by al charrakh et al, were P. aeruginosa was a predominant pathogen among various NFGNB [15]. In our study, P. aeruginosa showed increased prevalence the blaNDM gene (50%) followed by blaVIM gene (25%) and blaIMP gene (25%), these findings were similar to the study by Namaei et al, blaNDM gene (40%) followed by blaVIM gene (29%) and blaIMP gene (13%) [16,17]. In our study, for A. baumannii we observed an increased prevalence of blaOXA-23 gene(78%) followed by blaOXA-58 (56%) and blaNDM gene(33%).…”
Section: Discussionsupporting
confidence: 92%
“…However, a lower percentage of MBL prevalence was reported by Gupta et al ( 38 ) (21.4%). Furthermore, a higher percentage of MBL producers (80%) was reported by Namaei et al ( 39 ). In our study, the highest rate of MBL producers was observed in P. aeruginosa ( Table 4 ).…”
Section: Discussionmentioning
confidence: 70%
“…For colistin broth microdilution, Pseudomonas aeruginosa ATCC 27853 (MIC: 0.5-4 µg/mL) was used as negative control and an in-house Pseudomonas aeruginosa (MIC >16 µg/mL) was used as positive control. The isolates resistant to three or more antibiotic classes were labelled as MDR phenotype [ 19 ]. Descriptive analysis of all the observations is performed.…”
Section: Methodsmentioning
confidence: 99%